How Does the Use of Information Communication Technology Affect Individuals? A Work Design Perspective - Wang, Bin; Liu, Yukun; Parker, Sharon K. (Academy of Management Annals, 2020)
© Academy of Management Annals. People design and use technology for work. In return, technology shapes work and people. As information communication technology (ICT) becomes ever more embedded in today’s increasingly digital organizations, the nature of our jobs and employees’ work experiences are strongly affected by ICT use. This cross-disciplinary review focuses on work design as a central explanatory vehicle for exploring how individual ICT usage influences employees’ effectiveness and well-being. We evaluated 83 empirical studies. Results show that ICT use affects employees through shaping three key work design aspects: job demands, job autonomy, and relational aspects. To reconcile previous mixed findings on the effects of ICT use on individual workers, we identify two categories of factors that moderate the effects of ICT use on work design: user-technology fit factors and social-technology fit factors. We consolidate the review findings into a comprehensive framework that delineates both the work design processes linking ICT use and employee outcomes and the moderating factors. The review fosters an intellectual conversation across different disciplines, including organizational behavior, management information systems, and computer-mediated communication. The findings and the proposed framework help to guide future research and to design high-quality work in the digital era.